Mayo Cardiac Intensive Care Unit Admission Risk Score (M-CARS) validation test to assess mortality during treatment in Cardiovascular Care Unit (CVCU) patients at Haji Adam Malik Hospital - Siahaan, Basten Jeremiah; Hasan, Refli; Sitepu, Andika (Jurnal Kardiologi Indonesia, 2025)
In “Mayo Cardiac Intensive Care Unit Admission Risk Score (M-CARS) Validation Test to Assess Mortality During Treatment in Cardiovascular Care Unit (CVCU)Patients at Haji Adam Malik Hospital” (Indonesian Journal of Cardiology, 43(4), 137-43. https://doi.org/10.30701/ijc.1261), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1261. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1261